Bilateral Neonatal Testicular Torsion; Hidden Surgical Nightmare - Abbas, Tariq O.; Ali, Mansour (Frontiers in Pediatrics, 2018)
Perinatal testicular torsion is a relatively rare event that remains unrecognized in many situations and treated correctly only after an avoidable loss of time. Current management strategies for prenatal torsion include observation alone, delayed contralateral orchiopexy and emergent contralateral orchiopexy. Bilateral torsion is now being reported with more frequency and approximately a third of these patients have asynchronous torsion. Physical examination findings and imaging can be inaccurate to assess the contralateral testis in males born with perinatal torsion. We report a case of prenatal testicular torsion with incidentally discovered metachronous contralateral extravaginal testicular torsion. Therefore, immediate surgery is mandatory not only in suspected bilateral torsions but also in cases of possible unilateral torsions. Whenever possible, affected testes should be left back as some endocrine function may be retained.